Multimodal Magnetic Core–Shell Nanoparticles for Effective Stem‐Cell Differentiation and Imaging1. Issue 24 (6th May 2013) - Shah, Birju; Yin, Perry T.; Ghoshal, Shraboni; Lee, Ki‐Bum
<x xml:space="preserve">Abstract</x> Special delivery! The title system, composed of a highly magnetic core surrounded by a thin uniform gold shell, has been synthesized and applied to the magnetically facilitated delivery of genetic material (siRNA or plasmid DNA) into neural stem cells (NSCs) for controlling their neural differentiation in a spatiotemporally controlled, biocompatible manner.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>